An Integrated Public Health Approach to Interpersonal Violence and Suicide Prevention and Response. (November 2018) - Decker, Michele R.; Wilcox, Holly C.; Holliday, Charvonne N.; Webster, Daniel W.
Violence is a leading source of morbidity and mortality in the United States. In this article, we suggest a public health framework for preventing community violence, intimate partner violence and sexual violence, and suicide as key forms of interpersonal and self-directed violence. These types of violence often co-occur and share common risk and protective factors. The gender, racial/ethnic, and age-related disparities in violence risk can be understood through an intersectionality framework that considers the multiple simultaneous identities of people at risk. Important opportunities for cross-cutting interventions exist, and intervention strategies should be examined for potential effectiveness on multiple forms of violence through rigorous evaluation. Existing evidence-based approaches should be taken to scale for maximum impact. By seeking to influence the policy and normative context of violence as much as individual behavior, public health can work with the education system, criminal justice system, and other sectors to address the public health burden of interpersonal violence and suicide.